Setting of an endoscopic nasal reference point for surgical access to the anterior base through an anatomical study on cadavers - Zanuncio,Andressa Vinha (2016)
Abstract Introduction: Diseases of paranasal sinuses, nasal cavity, and skull base can be treated by endonasal operations using a nasal rigid endoscope. When conducting this kind of surgery, anatomical references are critical for safety. Objective: To measure the distance from the posterior wall of the maxillary sinus to the skull base, according to socio-demographic characteristics, and to detail an anatomical reference point for paranasal sinus operations and for an access to the anterior skull base, comparing anatomical variations between right and left sides, gender, height, weight, age, and ethnicity in cadavers. Methods: Measures were taken from the 90° angle (the starting point where deflection of the skull base begins to form the anterior wall of the sphenoid, also known as Δ90°) to the upper, middle, and lower points of the posterior wall of the maxillary sinus. This study used 60 cadavers aged over 17 years, and evaluated these bodies with respect to age, height, BMI, weight, gender, and ethnicity, comparing measurements of right and left sides. Results: The measurements were >1.5 cm in all cadavers and did not vary with age, height, weight, gender, and ethnicity on their right and left sides. The lack of association between the measurement from Δ90° to the upper, middle, and lower posterior walls of the maxillary sinus (categorical or quantitative) is noteworthy, considering the characteristics studied. Conclusion: The methodology defined the nasal point of reference, considering an absence of variation in the cadavers’ characteristics.